Versatile Use of Intraoperative Ultrasound Guidance for Brain Puncture. Issue 6 (8th October 2021) - Unal, Tugrul Cem; Gulsever, Cafer Ikbal; Sahin, Duran; Dagdeviren, Huseyin Emre; Dolas, Ilyas; Sabanci, Pulat Akin; Aras, Yavuz; Sencer, Altay; Aydoseli, Aydin
Abstract: BACKGROUND: Intraoperative ultrasound (iUS) is an effective guidance and imaging system commonly used in neuro-oncological surgery. Despite the versatility of iUS, its utility for single burr hole puncture guidance remains fairly underappreciated. OBJECTIVE: To highlight the simplicity, versatility, and effectiveness of iUS guidance in brain puncture by presenting the current case series and technical note collection. METHODS: We present 4 novel uses of iUS guidance for single burr hole brain puncture: cannulation of normal-sized ventricles, endoscopic third ventriculostomy (ETV) guidance, evacuation of interhemispheric empyema, and stereotactic biopsy assistance. RESULTS: All techniques were performed successfully in a total of 16 patients. Normal-sized ventricles were cannulated in 7 patients, among whom 5 underwent Ommaya reservoir placement and 2 underwent ventriculoperitoneal shunt placement for idiopathic intracranial hypertension. No more than 1 attempt was needed for cannulation. All ventricular tip positions were optimal as shown by postoperative imaging. iUS guidance was used in 5 ETV procedures. The working cannula was successfully introduced to the lateral ventricle, providing the optimal trajectory to the third ventricular floor in these cases. Interhemispheric subdural empyema was aspirated with iUS guidance in 1 patient. Volume reduction was clearly visible, allowing near-total evacuation of the empyema. iUS guidance was used for assistive purposes during stereotactic biopsy in 3 patients. No major perioperative complications were observed throughout this series. CONCLUSION: iUS is an effective and versatile guidance system that allows for real-time imaging and can be easily and safely employed for various brain puncture procedures.